Chemical composition and antifungal activity of Teucrium Leucocladum Boiss. essential oils growing in Egypt using two different techniques - Eman Mohamed Salah; Marwa Y. Issa; Tarik A. Mohamed; Mohamed-Elamir F. Hegazy; Soad H. Tadros; Noha Fathallah (SpringerOpen, 2024)
Abstract Background Teucrium Leucocladum Boiss. (TL) (family Lamiaceae), indigenous to Sinai, Egypt, and Mediterranean region, is considered a rich source of essential oils (EOs). This study aimed to extract the aerial parts essential oils utilizing hydro-distillation (HD) and microwave-assisted extraction (MAE), and analyze the volatile constituents by Gas Chromatography-Mass Spectrometry (GC/MS). The antifungal and cytotoxic potentials against Candida albicans (C. albicans) and non-small cell lung adenocarcinoma A549, triple-negative breast cancer MDA-MB-231 cell lines, respectively, were likewise estimated. Subsequently, the three main compounds were docked into the crystal structure of Candida albicans N-myristoyltransferase (NMT) with myristoyl-COA and peptidic inhibitor (PDB 1IYK), and predictions of human absorption, distribution, metabolism, and excretion (ADME) were performed to assess the drug-likeness of the compounds. Results The chemical profile consisted of monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons, and oxygenated sesquiterpenes. The MAE oil sample (TLM) yield was found to be double that of the HD oil sample (TLH). TLM afforded an inhibitory diameter (13 mm) comparable to the ketoconazole (20 mm), TLM 100 mg/mL showed the strongest antifungal potential against C. albicans. The cytotoxic assay revealed moderate activity against A549 and MDA-MB-231. In silico studies using molecular docking were processed on the major components in which nerolidol had the best-fitting energy to inhibit C. albicans (− 7.21 kcal/mol), while ADME results established a promising first step for the potential drug bioavailability. Conclusion In this research, essential oil acquired from the aerial parts proved to contain monoterpenes and sesquiterpenes, which are classes of compounds known for their versatile usage in medicine. In vivo studies on Teucrium Leucocladum Boiss. active metabolites against clinical strains of fungi need to be further studied, as do the effects of combining the active compounds with antifungal agents to combat antimicrobial resistance.